Registered psychiatric service use, self-harm and suicides of children and young people aged 0-24 before and during the COVID-19 pandemic: a systematic review - Yunus; Wan Mohd Azam Wan Mohd; Kauhanen, Laura; Sourander, Andre; Brown, June S. L.; Peltonen, Kirsi; Mishina, Kaisa; Lempinen, Lotta; Bastola, Kalpana; Gilbert, Sonja; Gyllenberg, David (BMC, 2026)
Background The COVID-19 pandemic has impacted on psychiatric symptoms of children and young people, but many psychiatric services have been disrupted. It is unclear how service use, self-harm and suicide has changed since the pandemic started. To gain timely information, this systematic review focused on studies based on administrative data that compared psychiatric service use, self-harm and suicide before and during the pandemic among children and young people. Methods and finding A systematic review of studies published in English from 1 January 2020 to 22 March 2021 was conducted, using the Web of Science, PubMed, Embase and PsycINFO databases. Increases or reductions in service use were calculated and compared using percentages. Of the 2,676 papers retrieved, 18 were eligible for the review and they provided data from 19 countries and regions. Most studies assessed changes during the early phase of the COVID-19 pandemic, from March to July 2020, and three assessed the changes until October 2020. Fifteen studies reported a total of 21 service use outcomes that were quantitively examined. More than three-quarters of the 21 outcomes (81%) fell by 5-80% (mean reduction = 27.9%, SD = 35%). Ten of the 20 outcomes for psychiatric emergency department (ED) services reduced by 5% to 80% (mean = 40.1%, SD = 34.9%) during the pandemic. Reductions in service use were also recorded for ED visits due to suicide ideation and self-harm, referrals to secondary mental health services, psychiatric inpatient unit admissions and patients receiving treatment for eating disorders. However, there were also some increases. Suicide rate and the number of ED visits due to suicide attempts have increased, and there was an increase in the number of treatment sessions in a service that provided telemedicine. Conclusion Most of the studies showed reductions in the use of psychiatric services by children and young people during the early phase of the pandemic and this highlighted potential delays or unmet needs. Suicide rate has increased during the second wave of the pandemic. Further studies are needed to assess the pattern of service use in the later phases of the COVID-19 pandemic.